Phlebotomine sand flies in Southwest Germany: an update with records in new locations - Hoffmann, Sandra; Jöst, Hanna; Heitmann, Anna; Lühken, Renke; Krüger, Andreas; Steinhausen, Irmgard; Brinker, Christine; Lorentz, Susanne; Marx, Michael; Schmidt-Chanasit, Jonas; Naucke, Torsten; Becker, Norbert (Parasites & vectors, 2020)
BackgroundVector-borne diseases (VBD) are of growing global importance. Sand flies are potential vectors for phleboviruses (family Phenuiviridae) including Toscana virus (TOSV), Sicilian virus, Sandfly fever, Naples virus, and Leishmania parasites in Europe. To date, only two phlebotomine species have been recorded for Germany: Phlebotomus perniciosus and Phlebotomus mascittii. This study updates the distribution and abundance of the two occurring species.MethodsAn entomological field study was carried out during 2015-2018 to assess the abundance of sand flies in Southwest Germany within the federal states Baden-Wuerttemberg (BW) and Rhineland-Palatinate (RLP). A total of 176 collection sites were examined using CDC light traps.ResultsA total of 149 individuals of P. mascittii were collected. During 2015-2018, P. mascittii was found at all sites known positive from previous studies and was detected at 15 additional sites previously unknown for the presence of sand flies. Although the environment has changed considerably in 30 years, no significant difference in sand fly dynamics and distribution was found. Phlebotomus perniciosus has only been trapped once since 2001.ConclusionsThis study showed that sand flies occur in different areas in Southern Germany where they had not been recorded previously. Therefore, it can be assumed that they are more widespread than expected. In addition, sand flies could be found over several years at the same trapping sites, indicating population stability. This supports the need for continued surveillance of possible vector populations and urgent clarification of the vector competence of P. mascittii.